Modelo estructural calibrado y análisis dinámico del Edificio Central del Instituto Costarricense de Electricidad - Cordero-Camacho, María Elena (Instituto Tecnológico de Costa Rica, 2017)
The building that serves as the headquarters of the Costa Rican Institute of Electricity (ICE, for its initials in Spanish) was built between 1969 and 1972. Due to its 40 plus years of service life, and the lack of a seismic code during its design and construction in Costa Rica, a structural evaluation is required to determine its structural integrity and to determine its remaining service life. The present work corresponds to the second stage of this ongoing structural evaluation, and consists on the elaboration of a structural model of ICE´s headquarters building, as well as its lineal dynamic analysis. The structural model from the present work will serve as the starting point for future definitive analysis. The structural model was elaborated utilizing the ETABS software suite, and is based on previous works and research carried out that compiled information on the status of the different structural elements, as well as the estimation of the existing gravitation loads (dead and live loads) that the structure is currently being subjected to. In order to guarantee the fidelity of the models behavior to that of the existing structure, it was calibrated using a technique based on estimating the dynamic properties of the existing structure. This technique involves the collection of the buildings oscillations due to environmental vibrations using accelerographs, and the calculation of its fundamental frequencies and periods from the collected data. Once the model was calibrated, a modal spectral analysis was carried out in order to compare the drifts obtained from the model to the limits established by the Seismic Code of Costa Rica in its 2010 edition.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Estructuras; Sismos; Edificios; Calibración; Construcción